Transporte de sólidos suspensos, nitrogênio, fósforo total dissolvido e a ictiofauna de riachos da sub-bacia do Paraná III. - Oliveira, Luciano Caetano de (2007)
The present study has as objective analyzes the transport of nutrients and the ichtyofauna of streams of the São Francisco Verdadeiro river micro-basin, in Marechal Cândido Rondon, Paraná, Brazil, six sampling stations were established in three streams (Curvado, Ajuricaba and Arroio Fundo) - one station at the mouth and other at the spring of the streams. Water samples were carried out between June 2005 and May 2006, totalizing 72 samples, in different stages of the hydrologic cycle, of evaluating spatial and temporal patterns during the period of June of 2005 and April of 2006 of the fish, bimonthly samplings were accomplished by the method of electric fishing in two sampling sites. The following variables were analyzed: temperature, pH, electric conductivity, dissolved oxygen, turbidity, suspension material, total phosphorus dissolved, orthophosphate, total nitrogen and amoniacal nitrogen. The Principal Components Analysis (PCA) discriminated the system in based on the largest values registered for the limnological variables that separated the periods influenced by droughts and rains. The collections resulted in 2,676 units pertaining to 29 species distributed in eight families. The spring stations presented a high density in number of individuals and larger diversity values, equitability and richness of species when compared to the mouth. However, the contribution of aloctone material contributed to the temporary structuring of the fish, reflex of the rainy period, which was not responsible for the space changes. It s worth safeguarding the importance of the appropriate handling of the basin, if it was the intention of preserving not only the aquatic biota, but the life around her, as well.